NILAI-NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERITA RAKYAT DAERAH JAMBI KARYA H. ZUKRI NAWAS - Erlina Zahar; Nurani Lumban Tobing (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research aims to describe the educational character values in the collection of Cerita Rakyat Daerah Jambi  by H. Zukri Nawas. There 9 aspects of educational character values; namely honesty, bravery, trustworthy, fair, thoughtful, responsible, confident, hardwork, and tolerance aspects. This study included a qualitative type of descriptive. Based on the results of data analysis, it is known that there are 50 quotations which are divided into 9 aspects of educational character as follows: 1) There are 5 quotations of honesty (always talking honestly, working honestly, and admitting any mistakes honestly); 2) there are 11 quotations of bravery aspect (having courage when starting something new and facing evil); 3) there are 5 quotations of trustworthy aspect (have an attitude of trust when carrying out their duties and obligations by exemplify good works; 4) there are 3 quotations of fairness aspect (fair in earning rights under its obligations); 5) there are 4 quotations of thoughtful aspect (have an attitude and right in the act accompanied by a mature thought; 6) there are 7 quotations of being responsible aspect (have a responsibility attitude when doing a job well done); 7) there is 1 quotation of confident aspect  (having a high confidence when someone else is undoing it but he still remains at his own); 8) there are 8 quotations of hardworking aspect (have a hard work attitude that always try to get something he wants), and 9) there are 6 quotations of tolerance aspect (have a mutual respect). It can be concluded that there are some educational values found in the collection of Cerita Rakyat Daerah Jambi  by H. Zukri Nawas. The aspects are honesty, bravery, trustworthy, fair, thoughtful, responsible, confident, hardwork, and tolerance.